Baraba Waldsteppe, Russland. Westsibirien. Neues zu Andronovo-Fundplätzen in der nördlichen Baraba Steppe. Die Arbeiten der Jahre 2020 und 2021 - Reinhold, Sabine; Eger, Jana; Kobeleva, Lilja S.; Molodin, Vjačeslav I.; Mylnikova, Lûdmila N. (e-Forschungsberichte des DAI, 2022)
The steppe and forest-steppe zone of Western Siberia is one of the core regions of the Eurasian continent. Among the sites in the Siberian Forest steppe, those of the Andronovo (Fёdorovo) cultural community occupy a special position. In the northern Baraba Forest steppe many burial sites of these communities are known, including the large necropolises of Tartas 1, a long-term joint excavation of the Eurasia-Department and the Institute of Archaeology and Ethnology in Novosibirsk. However, nearly no settlements associated with the necropolises were known and it was a mystery, where the population lived at that time. In 2020, such an Andronovo (Fёdorovo) settlement site was discovered near the village of Vengerovo, Novosibirisk region; excavations started in 2021. The location of this site was surprising. Unlike other settlements, the site of Tartas 5 is located not on the riverbank but in the floodplain of the Tartas River. The site revealed a stratigraphy with two cultural horizons and sterile sediments in-between, stemming from repeated flooding of the plain. The lower stratum is associated with the Andronovo (Fёdorovo) cultural community, the upper layer dates most likely to the Iron Age. A short overview of complexes, layers, and the animal bone collection analyzed in 2021 is given. First dates place into the 15th/14th century BCE.